2011
DOI: 10.1111/j.1524-4741.2011.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Lesions with Imaging-Histologic Discordance During 16-Gauge Core Needle Biopsy System: would Vacuum-Assisted Removal get Significantly More Definitive Histologic Diagnosis Than Vacuum-Assisted Biopsy?

Abstract: The aim of this study was to determine the role of vacuum-assisted biopsy (VAB) in patients with ultrasound imaging-histologic discordance during 16-gauge core needle biopsy (CNB) and to compare VAB with vacuum-assisted removal (VAR) in diagnostic accuracy in patients with ultrasound imaging-histologic discordance. From January 2006 to October 2008, a consecutive biopsy was performed on 1532 lesions with ultrasound-guided 16-gauge CNB. Sixty two lesions were considered to be ultrasound imaging-histologic disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…[15][16][17][18] Among lesions with ultrasonographyehistologic discordance, 21.4% are upgraded in the pathological diagnosis after VAB, according to Li et al 19 Furthermore, it has also been reported that VAB might be valuable for definitive diagnosis when pathological results with CNB are discordant with imaging findings. [19][20][21] Accordingly, the use of VAB is supported by many physicians, especially for small lesions. 14,22,23 However, we have to keep in mind that VAB is based on the same concept as CNB: a partial sampling of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Among lesions with ultrasonographyehistologic discordance, 21.4% are upgraded in the pathological diagnosis after VAB, according to Li et al 19 Furthermore, it has also been reported that VAB might be valuable for definitive diagnosis when pathological results with CNB are discordant with imaging findings. [19][20][21] Accordingly, the use of VAB is supported by many physicians, especially for small lesions. 14,22,23 However, we have to keep in mind that VAB is based on the same concept as CNB: a partial sampling of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there was a significant difference in the agreement between mass and non-mass lesions for 18G CNB. This indicates that for smaller caliber CNB performed on non-mass lesions, especially 18G, the diagnosis value is lower than biopsies using a larger core needle or vacuum-assisted CNB [31]. …”
Section: Discussionmentioning
confidence: 99%
“…The frequency of imaging-histologic discordance has been reported to be 1-6%, and several studies have reported imaging-histologic discordance following stereotactic CNB ( 4 , 8 , 9 ) and US-guided CNB ( 1 , 6 , 8 , 10 , 11 , 12 ). These reports show malignancy rates of 6.8-29.3% in imaging-histologic discordant lesions during US-guided biopsy ( 1 , 6 , 10 , 12 , 13 , 14 , 15 ), suggesting that rebiopsy of those lesions will yield benign pathology in approximately 70.7-93.2% of cases. Considering the large percentage of benign pathology at rebiopsy, Kim et al ( 12 ) used vacuum-assisted removal (VAR) on discordant cases for a definitive diagnosis.…”
Section: Introductionmentioning
confidence: 94%
“…Some investigators have reported results of VAR management of imaging-histologic discordant lesions ( 13 , 15 ). However, the number of patients in those studies was small (n = 28 and 55), and they used a 16-gauge core biopsy needle instead of a 14-gauge core biopsy needle ( 13 , 15 ). Moreover, their follow-up period was 12 months, which is insufficient to confirm the absence of false-negative biopsy results after VAR.…”
Section: Introductionmentioning
confidence: 99%